Future flooding tolerant rice germplasm: Resilience afforded beyond Sub1A gene - Anumalla, Mahender; Khanna, Apurva; Catolos, Margaret; Ramos, Joie; Sta. Cruz, Ma Teresa; Venkateshwarlu, Challa; Konijerla, Jaswanth; Pradhan, Sharat Kumar; Dash, Sushanta Kumar; Das, Yater; Chowdhury, Dhiren; Chetia, Sanjay Kumar; et al. (Wiley, 2025)
Developing high-yielding, flood-tolerant rice (Oryza sativa L.) varieties is essential for enhancing productivity and livelihoods in flood-prone ecologies. We explored genetic avenues beyond the well-known SUB1A gene to improve flood resilience in rice. We screened a collection of 6274 elite genotypes from IRRI's germplasm repository for submergence and stagnant flooding tolerance over multiple seasons and years. This rigorous screening identified 89 outstanding elite genotypes, among which 37 exhibited high submergence tolerance, surpassing the survival rate of SUB1A introgression genotypes by 40%–50%. Thirty-five genotypes showed significant tolerance to stagnant flooding, and 17 demonstrated dual tolerance capabilities, highlighting their adaptability to varying flood conditions. The genotypes identified have a broader genetic diversity and harbor 86 key quantitative trait loci (QTLs) and genes related to traits such as grain quality, grain yield, herbicide resistance, and various biotic and abiotic traits, highlighting the richness of the identified elite collection. Besides germplasm, we introduce an innovative breeding approach called “Transition from Trait to Environment” (TTE). TTE leverages a parental pool of high-performing genotypes with complete submergence tolerance to drive population improvement and enable genomic selection in the flood breeding program. Our approach of TTE achieved a remarkable 65% increase in genetic gain for submergence tolerance, with the resulting fixed breeding genotypes demonstrating exceptional performance in flood-prone environments of India and Bangladesh. The elite genotypes identified herein represent invaluable genetic resources for the global rice research community. By adopting the TTE approach, which is trait agonistic, we establish a robust framework for developing more resilient genotypes using advanced breeding tools.